Effect of maternal age, embryo number and quality on pregnancy outcome during frozen embryo transfer cycle - Gao, Wenyi; Tang, Weiwei; Li, Caixia; Deng, Yun; Chen, Yao; Zhang, Yanru; Pan, Xiaohong; Yang, Chunyan; Liu, Yuanyuan; Xiong, Fang; Jin, Xin (Frontiers in Endocrinology, 2025)
BackgroundTo investigate the effects of maternal age, the number of transferred embryos, and embryo quality on pregnancy-related outcomes in frozen-thawed embryo transfer cycles.DesignA retrospective cohort study was conducted on 1031 frozen-thawed embryo transfer cycles enrolled at our hospital from January 2015 to December 2021.ResultsIn the pregnant group, maternal age was significantly lower compared to the non-pregnant group; additionally, both the number of transferred embryos and the number of high-quality embryos transferred were significantly higher in the pregnant group. Women older than 35 years exhibited significantly lower clinical pregnancy rate (p < 0.05), implantation rate (p < 0.001), and live birth rate (p < 0.01). A higher number of transferred embryos was associated with significantly increased clinical pregnancy rate (p < 0.001) and live birth rates (p < 0.001). When transferring two embryos, higher numbers of 7–9 cell embryos (p < 0.01) and grade 1 embryos (p < 0.001) were positively correlated with improved clinical outcomes, while increased transfers of fragmented (p < 0.05) and uneven embryos (p < 0.05) were negatively associated with these outcomes.ConclusionMaternal age, the number of transferred embryos, and embryo quality significantly influence pregnancy outcomes in frozen-thawed embryo transfer cycles. Clinicians should carefully tailor transfer plans based on individual patient characteristics and select optimal embryos for transfer to maximize success rate.